2022
DOI: 10.1017/jns.2022.3
|View full text |Cite
|
Sign up to set email alerts
|

A live yeast supplementation to gestating ewes improves bioactive molecule composition in colostrum with no impact on its bacterial composition and beneficially affects immune status of the offspring

Abstract: Colostrum quality is of paramount importance in the management of optimal ruminant growth and infectious disease prevention in early life. Live yeast supplementation effect during the last month of gestation was evaluated on ewes’ colostrum composition. Two groups of ewes (n = 14) carrying twin lambs were constituted and twins were separated into groups (mothered or artificially fed) 12 h after birth. Nutrient, oligosaccharides (OS), IgG and lactoferrin concentrations were measured over 72 h after lambing, and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…During the first days after birth, colostrum, providing energy and immunity, is indispensable for newborn puppies to deal with the challenging transition from intrauterine to extrauterine life (19,87). Many studies in pigs support that live yeast supplementation during gestation and/or lactation improves the quality of colostrum (16, [88][89][90][91]. In the current study, the SB-1079 supplementation had no effect on the immune composition of the colostrum.…”
Section: Group Comparisonmentioning
confidence: 63%
See 1 more Smart Citation
“…During the first days after birth, colostrum, providing energy and immunity, is indispensable for newborn puppies to deal with the challenging transition from intrauterine to extrauterine life (19,87). Many studies in pigs support that live yeast supplementation during gestation and/or lactation improves the quality of colostrum (16, [88][89][90][91]. In the current study, the SB-1079 supplementation had no effect on the immune composition of the colostrum.…”
Section: Group Comparisonmentioning
confidence: 63%
“…Sialic acid has been described as increasing in gestating women, being largely involved in the milk oligosaccharides synthesis, and crossing the placenta to participate to in utero body growth and brain development (98). Dunière et al (91) reported that a supplementation of gestating ewes with a live yeast resulted in significantly higher levels of colostral N-glycolylneuraminic acid. In our study, the decrease in number of LBW puppies as well as the trend to have more sugars in the colostrum are consistent with a modulation of the amino-sugar metabolism.…”
Section: Group Comparisonmentioning
confidence: 99%
“…In agreement with these observations, lower serum IgG has been often observed in ruminants fed milk replacer [ 18 ]. In addition to bioactive proteins, colostrum includes oligosaccharides which probably provide adequate substrates to the pioneer gut bacteria [ 30 ]. Limited colostrum intake may then also delay the bacterial colonization of the intestine, possibly leaving the newborn vulnerable to infections during the preweaning period.…”
Section: Discussionmentioning
confidence: 99%
“…In ewes, supplementation with live yeast during the last month of gestation increased colostrum IgG and other bioactive molecules (Dunière et al 2022). This improvement in colostrum composition translated into higher serum IgG in lambs born from supplemented ewes and kept with their mothers for only 12 h, while no effect of supplementation was observed in the lamb group that stayed with the dams (Dunière et al 2022).…”
Section: Microbial Productsmentioning
confidence: 94%
“…In ewes, supplementation with live yeast during the last month of gestation increased colostrum IgG and other bioactive molecules (Dunière et al 2022). This improvement in colostrum composition translated into higher serum IgG in lambs born from supplemented ewes and kept with their mothers for only 12 h, while no effect of supplementation was observed in the lamb group that stayed with the dams (Dunière et al 2022). In dairy cows, supplementation with a yeast fermentation product during the transition period enhanced mucosal immunity and humoral immune response, without a positive effect on colostrum IgG (Yuan et al 2015).…”
Section: Microbial Productsmentioning
confidence: 99%